Challenges for Holistic Engineering Education Development in India - Zakir Husain; Deepak Kumar (International Journal of Evaluation and Research in Education (IJERE), 2014)
The new challenges for engineering education go more than the need to keep students abreast of cutting edge technology and calls for a better equilibrium in the various areas of engineering. There is considerable concern that upholding of the old standard by engineering institutions will all but degrade the quality of engineers as well as difficulty in adapting to the growing difficulties of the worldwide marketplace globally. This requires the new development model for the holistic growth of engineering education. However, adaptation of new development model will not be easy since lots of our research universities are faced with monetary pressures. Indian government has made significant contribution toward this growth phase for the development of nation. This paper addresses for an assessment study of the methods developed by reputed engineering institutions in India to lay the foundation for future engineering education. The looking forward segment provides suggestions and plans for engineering education in India.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5580